Simultaneous modeling of developer behavior and land prices in UrbanSim - Daniel Felsenstein; Eyal Ashbel (Journal of Transport and Land Use)
A strong inter-dependence exists between the decision to develop land and the expected returns to be gained from that development. Current practice in UrbanSim modeling treats developer behavior and the emergence of land prices as independent processes. This assumes that land prices are exogenous to the interaction between buyers and sellers—an assumption that is difficult to sustain in urban economics and real estate research. This paper presents an attempt to model the two processes as occurring simultaneously. Using the UrbanSim model for metropolitan Tel Aviv, we compare the results of forecasts for densities (residential and non-residential) and land values for the period 2001–2020. Our results show that simultaneous estimation tends to produce more accentuated outcomes and volatile trends. The validity of these results and the implications of this approach in the wider context of land use modeling are discussed.